2014
DOI: 10.1248/bpb.b14-00170
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-<i>O</i>-GlcNAcylation Inhibits the Induction of Heat Shock Protein 70 (Hsp 70) by Sodium Arsenite in HeLa Cells

Abstract: O-Linked β-N-acetylglucosamine-modification (O-GlcNAcylation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…[ 41 ] In addition, the work by Miura suggested that O‐GlcNAcylation did not regulate the nuclear translocation and phosphorylation of heat shock Factor 1. [ 85 ] It is therefore plausible that O‐GlcNAc modulates protein nucleocytoplasmic shuttling in many ways, including through changing protein conformation, [ 86 ] activating complex signaling pathways, [ 87 ] and generating extensive crosstalk with other posttranscriptional modifications. [ 88 , 89 ] The need for a better understanding of the functions and mechanisms of O‐GlcNAcylation remains.…”
Section: Discussionmentioning
confidence: 99%
“…[ 41 ] In addition, the work by Miura suggested that O‐GlcNAcylation did not regulate the nuclear translocation and phosphorylation of heat shock Factor 1. [ 85 ] It is therefore plausible that O‐GlcNAc modulates protein nucleocytoplasmic shuttling in many ways, including through changing protein conformation, [ 86 ] activating complex signaling pathways, [ 87 ] and generating extensive crosstalk with other posttranscriptional modifications. [ 88 , 89 ] The need for a better understanding of the functions and mechanisms of O‐GlcNAcylation remains.…”
Section: Discussionmentioning
confidence: 99%